Виды рода Agapanthus L’Herit. в коллекционном фонде Донецкого ботанического сада НАН Украины - Владимирова, Л.В.; Новохатская, О.В. (Промышленная ботаника, 2002)
The results of studies (1981-2001) of the genus Agapanthus L’Herit. species grown in the Donetsk Botanical Gardens conservatories are summarized in the article, as well as the information from the literary sources on the introduction of this genus species into the conservatories. The data are considered as for the growth and development of Agapanthus africanus (L.) Hoffmgg and A.praecox Willd. under the conditions of the DBG greenhouses.